Peningkatan Ketrampilan Guru SD dalam Pembuatan Video Pembelajaran dengan Menggunakan Telepon Cerdas - Slamet Riyadi; Erwan Sudiwijaya; Apriliya Kurnianti; Arif Bintoro Johan (Universitas Muhammadiyah Semarang, 2023)
Learning in digital era demands innovation of learning materials where video is one of the attractive materials. Unfortunately, many teachers don't have skills to make learning videos, including some teachers at the Muhammadiyah Elementary School in Godean. Therefore, this program aims to improve the skills of partners in making learning videos. The main equipment used is a cell phone which is owned by all teachers so there is no need to procure additional equipment. The steps carried out are preparation, implementation and evaluation. Preparations have been made by discussing with partners about the training to be held. The training was completed on April 9, 2022 at the UMY Information Technology Laboratory, attended by 37 teachers from three Muhammadiyah elementary schools in Godean District. Participants received theory and immediately practiced making videos using their respective cell phones. Training evaluation was carried out using pre and post tests as well as observation. This program has succeeded in increasing teachers' knowledge and skills in making learning videos with a significant increase in pre-test and post-test results of 54.7%.